Food and feeding habits of the Rhesus macaque (Macaca mulatta) and their interactions with humans at Charmuguria, Madaripur, Bangladesh - Baruri, Dipa; H Khan, M Monirul; Ferdiousi, Jannatul (Jahangirnagar University Journal of Biological Sciences, 2025)
This study explores the food and feeding habits of the Rhesus macaque (Macaca mulatta) and their interactions with humans living in the urban landscape of Charmuguria, Madaripur, Bangladesh, from April to October 2023. Transect and scan sampling methods were followed to investigate the diet and feeding habits of Rhesus macaque. Also, a pre-designed questionnaire was used to interview local people and visitors in order to understand their response to macaques. Our study showed that about 70% of the diet came from provisioning, 19% from plants and the remaining 11% was from insects. Secondly, a total of 29.6% of people experienced close contact with the macaque, while about 18.2% people of biting and scratching. About 54.6% of respondents reported property damage to crops, vegetables, fruits and plants. More than half (52.3%) of the people thought that humans are harmful to macaques, while the remaining respondents (47.7%) mentioned that macaques are harmful to humans because of their aggressive behaviour and loss of property. About 88.6% of respondents suggested the need for macaque conservation. Jahangirnagar University J. Biol. Sci. 13(1 & 2): 1-10, 2024 (June & December)